An efficient framework for the inelastic performance assessment of structural systems subject to stochastic wind loads. (15th January 2019) - Chuang, Wei-Chu; Spence, Seymour M.J.
Highlights: An efficient model for the inelastic analysis of wind-excited systems is presented. The framework is based on a fully stochastic description of the wind loads. The approach is centered on probabilistic dynamic shakedown theory. Inelastic collapse probability is integrated with modern performance-based design. A case study is presented demonstrating the potential of the proposed framework. Abstract: The modeling and estimation of the inelastic response of wind excited structures is attracting growing interest with the introduction of performance-based wind engineering. While frameworks based on direct integration have been widely adopted in earthquake engineering for estimating inelastic responses, the significantly longer duration of typical windstorms, as compared to seismic events, makes this approach extremely computationally challenging in the case of wind excited systems. This is especially true in the case of modern performance-based wind engineering frameworks, which are based on probabilistic metrics estimated through simulation and therefore repeated evaluation of the system. This paper addresses this challenge through the development of a simulation framework based on dynamic shakedown theory. In particular, an efficient path-following algorithm is proposed for estimating not only the shakedown multipliers, but also the plastic strains and deformations associated with occurrence of the state of shakedown. The efficiency with which this information can be estimated for any given wind load time history enables the development of a simulation-based framework, driven by general stochastic wind load models, for the estimation of the system-level inelastic performance of the structure. The validity and practicality of the proposed framework is illustrated on a large-scale case study.